PLOV IS AN IMPORTANT PART OF THE UZBEK NATIONAL ETHNIC CULTURE - Mirtursunov O.R; Reimnazarova G.D; Sharipova P.A; Don A.N (Western European Studies, 2024)
The article describes a traditional dish, plov, palov or pilaf, which is an important part of the national ethnic culture of Uzbekistan. The characteristics of the components, necessary items for its preparation are given. Detailed information on the nutritional value of the main products: carrots, meat. Comparative characteristic of mutton and beef is considered. Recommendation of the use of pilaf as a dietary dish in a number of patients with various diseases
Keywords: uzbek; plov; pilaf; ethnic; culture